The Influence of Instagram @Infokopibdl’s Communication Style on Online Engagement - Rini Oktaviony; Hanindyalaila Pienrasmi; M. Denu Poyo (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to examine the influence of communication style on online engagement among the followers of the Instagram account @infokopibdl. The research addresses how a social media brand’s communication approach shapes digital engagement levels. Using a quantitative method, data were collected from 100 respondents through questionnaires. The relationship between variables was analyzed using simple linear regression techniques. The results indicate that the communication style employed by @infokopibdl has a positive and significant effect on online engagement. A friendly, polite, and interactive communication style enhances audience participation, specifically in the form of likes, comments, and content sharing. The study concludes that communication style is a strategic factor in fostering digital interaction. Practically, social media managers are encouraged to maintain consistency in style and use accessible language to build emotional closeness with audiences. Academically, this research provides empirical evidence within the field of communication studies regarding the role of stylistic approach in strengthening brand-audience relationships on digital platforms.